RASIO KEUANGAN DAN AUDIT REPORT LAG: PERAN INSTITUTIONAL OWNERSHIP SEBAGAI PEMODERASI - Ahmad Bebin Najmuddin; Melisa Anggraini; Dwi Hayu Estrini; Michaela Purnama Tan (Jurnal Ilmiah Fokus Ekonomi, Manajemen, Bisnis & Akuntansi (EMBA), 2025)
This study aims to examine the effect of financial ratios consisting of solvency (DER), profitability (ROA), and liquidity (CR) on audit report lag (AUDLAG), with institutional ownership serving as a moderating variable. The research data were obtained from the financial statements of companies listed on the Indonesia Stock Exchange (IDX) over a specified observation period, using the Moderated Regression Analysis (MRA) method. The results reveal that solvency and liquidity have no significant effect on audit report lag, while profitability has a negative and significant effect, indicating that higher profitability is associated with a shorter audit completion time. The moderation test shows that institutional ownership does not moderate the relationship between solvency and profitability with audit report lag, but it strengthens the effect of liquidity in accelerating the audit completion process. These findings support agency theory, suggesting that institutional ownership plays an important role as an effective monitoring mechanism to enhance transparency and efficiency in financial reporting. This study contributes to the corporate governance literature by providing empirical evidence on the role of institutional ownership in accelerating the audit process and reducing audit report lag.